A Study of Aisyiyah in Promoting Women’s Muslim Community in Banten Province: Its Ideology, Works, and Challenges - Ila Amalia (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2017)
This study examines the role of Aisyiyah, as one of the Islamic women organizations, in improving the status of women in Banten province. As an organization that has been established for almost a century Aisyiyah has given great and influential contributions toward the women’s development. This study focus on the ideology that Aisyiyah convey in running its organization, which is based on the teaching of the Holy Qur’an and Hadith (the sayings of the Prophet Muhammad SAW). The data were taken from the interview with the members of Aisyiyah Banten organization, publication, and documentation. The techniques used to collect the data were through in-depth interview, survey, and participatory observation. According to Aisyiyah men and women are equal in sight of Allah and have the same obligation in committing goodness. In doing its activities Aisyiyah keeps the slogan amal ma’ruf nahi munkar (commanding the goods and forbidding evil) based on the Holy Qur’an and Hadith. Aisyiyah has focused its activity in many sectors as education, health, and social welfare which are considered as women’s domain. During its development Aisyiyah has faced many challenges due to the social and political condition in the society. Lack of cadres, slow regeneration process, and its relationship with Muhammadiyah organization, as its parent organization, are among those challenges